(untitled) (Palíndromo, 2021)
In this essay, one narrates an iconological research experience on Warburg Institute Photographic Collection revolving around a photograph with no sources from the London collection, herein referred as “picture with no source”. The narrative revolves around questions relating to the historiographical process and the research experience in digital and physical collections, inquiring about the condition of the image and the text as processes influenced by the relationship between body and memory, logos and pathos. This paper starts on the case study of an image, and the referential search for narrative elements of the personifications of the goddesses Fortuna and Venus – and of the visual relations established between them, especially after the 15th century. One raises questions about the methodology of the art historian in face of the image, and of the epistemology of an iconological research, arguing that it can be seen as a process of narrative creation and of tensions between body, word, and image – hence, as an aesthetic experience. The essay also dialogues with Aby Warburg, Edgar Wind, and Monica Centanni.